Designing of Learning Media in Productive Lesson by Using Human Computer Interaction (HCI) Approach - Agustina Srirahayu; Arifki Dimas Sulistianto; Fajar Suryani (LPPM Universitas Duta Bangsa Surakarta, 2019)
State Vocational School 1 Miri opened the department of multimedia with one of the productive subjects of multimedia learning competencies including Image Capturing Production, Graphic Design Printing, Audio Video, 2D and 3D Animation, PKK (Entrepreneurship Creative Products), and Computer Assembly. Productive subjects 2D and 3D animation is one of the applied subjects of theoretical practice that focuses on the application of tweening animation techniques. To produce a good animated film, learning theory and practice given in class is not enough, additional materials and tools are needed that are interestingly packaged and can be used as learning media for students to better understand how to make the right animation. Android-based learning media design aims to produce an application interface that is easy to use, comfortable, and easy for users to operate the learning media. The design of instructional media with the HCI approach helps the developer in achieving user friendly designs according to HCI factors in Mobile-based applications. Based on observations made in class XI MM 2 with a total of 36 students, all students already have an Android smartphone. Seeing this potential, learning media by utilizing smartphones is by making an Android-based learning media design.